Me and my amazing body - Sweeney, Joan, 1930-; Cable, Annette (New York : Dragonfly Books/Crown, 2000)
A girl describes how her skin, bones, muscles, brain, blood, heart, lungs, and stomach receive energy and function as parts of her body.
Appraisal-Science Books for Young People
Booklist
School Library Journal
3.2
K-3.
K-3
Keywords: Human anatomy -- Juvenile literature; Human anatomy; Human body; Human physiology; Human anatomy; Human body; Physiology